Medical Students Experience with Problem-Based Learning in Asia: A Literature Review - Caesario, Michael (The Journal of The Indonesian Medical Students Association, 2010)
Since its introduction in 1969, problem-based learning (PBL) has revolutionized medical education around the world. Medical schools in Asia had started to apply PBL to their curriculum although PBL itself has a controversial history and had not yet proven to be superior to conventional curriculum. Several studies reported that medical students in Asia were gaining benefits from PBL such as improvement in communication and problem-solving skill and increasing interest in topics being studied. Same studies also reported problems such as low participation during discussion, uncomfortable feeling with independent learning method, and environment which was not conductive for discussion. These problems might be resulted from faculty and students cultural background and their unfamiliarity with PBL. However, there are evidences which showed that Asian students are able to adapt to PBL. In implementing PBL, the faculty must be prepared and able to be flexible in action. Further research is needed to reveal factors that hinder students; learning in PBL.ÃÂ Key words: problem-based learning, medical education, culture, Asia